2012
DOI: 10.4049/jimmunol.1201889
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Associated Macrophages Promote Invasion while Retaining Fc-Dependent Anti-Tumor Function

Abstract: Tumor-associated macrophages (TAMs) have been shown to promote tumor progression, and increased TAM infiltration often correlates with poor prognosis. However, questions remain regarding the phenotype of macrophages within the tumor and their role in mAb-dependent cytotoxicity. This study demonstrates that whereas TAMs have protumor properties, they maintain Fc-dependent anti-tumor function. CD11b+CD14+ TAMs isolated from primary human breast tumors expressed activating FcγRs. To model breast cancer TAMs in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
96
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(106 citation statements)
references
References 59 publications
8
96
1
1
Order By: Relevance
“…Recent studies have shown that TAM-like PBMo-derived macrophages stimulated with TCM such as those found in breast, ovarian, and colorectal cancer produced these factors. 16,[38][39][40] In the present study, GDF15 was upregulated in PBMo-derived macrophages stimulated with TECM, whereas, to our knowledge, it has not been reported that TAM-like PBMo-derived macrophages stimulated with other TCMs secreted GDF15. Expression of GDF15 was not detected in cytokine-induced M2-polarized macrophages such as IL-4 and IL-13 (Supplementary Figure 1).…”
Section: Gdf15 Increased the Growth Of The Escc Cell Lines By Triggercontrasting
confidence: 45%
“…Recent studies have shown that TAM-like PBMo-derived macrophages stimulated with TCM such as those found in breast, ovarian, and colorectal cancer produced these factors. 16,[38][39][40] In the present study, GDF15 was upregulated in PBMo-derived macrophages stimulated with TECM, whereas, to our knowledge, it has not been reported that TAM-like PBMo-derived macrophages stimulated with other TCMs secreted GDF15. Expression of GDF15 was not detected in cytokine-induced M2-polarized macrophages such as IL-4 and IL-13 (Supplementary Figure 1).…”
Section: Gdf15 Increased the Growth Of The Escc Cell Lines By Triggercontrasting
confidence: 45%
“…4 Furthermore, these mw may protect MM cells from chemotherapy drug-induced apoptosis. 5 Remarkably, tumor-associated mw may still induce Fc-dependent anti-tumor activity, 40 supporting a role for DARA-induced phagocytosis in the BM. Another approach is the combination with drugs regulating anti-phagocytic signals.…”
Section: Discussionmentioning
confidence: 99%
“…antibodies is reversed [109][110][111][112][113][114][115]. A lymphoma patient study showing that high TAM infiltration correlates with improved prognosis after a rituximab-containing regimen, but worsened prognosis without rituximab, supports these observations [116].…”
Section: Innate Immune Cellsmentioning
confidence: 81%